Determination of orientin in Trollius chinensis using ultrasound-assisted extraction and high performance liquid chromatography: Several often-overlooked sample preparation parameters in an ultrasonic bath - Wei, Mengxia; Yang, Lei (Journal of Chromatography A, 2017)
•Characterization of ultrasonic bath via phytomedicine extraction has been attempted.•Several often ignored and conventiational experimental conditions were investigated.•Ultrasound intensity in ultrasonic bath matches with extraction of orientin yield.•Characterization results enable further understanding of the ultrasonic bath. The erratic pressure intensities and cavitation exhibited in an ultrasonic bath pose various during practical application. To achieve the most efficient experimental design, this manuscript aims to discover violently sites that are subject to the effect of slight changes in position on cavitation and ultrasound intensity distributed in the ultrasonic bath. In addition, optimization several often over-looked ultrasound parameters and experimental conditions, are intended to place the reaction vessel properly and operate under suitable experimental conditions to obtain the maximum yield of target analyte. In this study, an investigation of the various ultrasound intensities and cavitation in ultrasonic bath space were conducted with the help of the orientin yield using ultrasound-assisted extraction. Conventional parameters such as the volume fraction of ethanol, liquid-solid ratio, ultrasound irradiation power, time and frequency, and reaction temperature were investigated, all of which affect the extractive yield factors. Also several often over-looked parameters such as the extraction vessel position in the ultrasonic bath base, the distance between the bottom of the extraction vessel and the ultrasonic bath base, the diameter, the shape and the texture of the extraction vessel, height of the liquid medium and the ultrasound propagating medium salt concentration in the ultrasonic bath were tested exhaustively in this study. These results can therefore serve as a guide to optimize the usage of the ultrasonic bath for future applications.